2020
DOI: 10.1002/pa.2449
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric effects of monetary policy shocks on output growth in Nigeria: Evidence from nonlinear ARDL and Hatemi‐J causality tests

Abstract: Given the importance of output growth in Nigeria and the need for monetary policy decisions to be guided by the knowledge of the asymmetric effects of positive and negative monetary policy shocks, this study investigates the asymmetric effects of monetary policy shocks on output growth in Nigeria using quarterly data from 1981Q1 to 2018Q4. The study employs the recently developed Lee and Strazicich unit root test with structural breaks, Nonlinear ARDL, and the Hatemi‐J causality tests. The result reveals the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
(55 reference statements)
1
18
0
Order By: Relevance
“…The pandemic has affected energy consumption patterns and impacted globalization and tourism to rethink innovation for sustainable recovery strategies ( Usman et al., 2020 ). The pandemic has influenced stock markets and caused inflation ( Goshit et al., 2020 ; Dabwor et al., 2020 ). The pandemic has also effected governments budgets for agricultural expenditures on household welfare plans ( Iorember and Jelilov, 2018 ).…”
Section: International Tourism: Regions Contribution To the Service Industrymentioning
confidence: 99%
“…The pandemic has affected energy consumption patterns and impacted globalization and tourism to rethink innovation for sustainable recovery strategies ( Usman et al., 2020 ). The pandemic has influenced stock markets and caused inflation ( Goshit et al., 2020 ; Dabwor et al., 2020 ). The pandemic has also effected governments budgets for agricultural expenditures on household welfare plans ( Iorember and Jelilov, 2018 ).…”
Section: International Tourism: Regions Contribution To the Service Industrymentioning
confidence: 99%
“…According to expert estimations, shutdowns of transportation and economic activities in this pandemic will lower global emissions for the first time since the world financial crisis of 2008 (84,(98)(99)(100)(101). The pandemic has affected demand for renewable energy consumption, trade on environmental quality, and human capital (102)(103)(104).…”
Section: Environmental Impactsmentioning
confidence: 99%
“…The pandemic has also affected environmental sustainability adversely and disrupted economic activities worldwide ( Goshit and Iorember, 2020 ; Iorember et al, 2020 , 2021 ; Jelilov et al, 2020 ; Usman et al, 2020 ). Recent researches have shown that the response of monetary aggregated necessary to support industrial performance within the pandemic period is weak relative to the period before the pandemic ( Abachi and Iorember, 2017 ; Iorember et al, 2019 ; Usman et al, 2019 ; Dabwor et al, 2020 ; Goshit et al, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%